If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4c + -3(c + -6) = 2 + 2 + 2c Reorder the terms: 4c + -3(-6 + c) = 2 + 2 + 2c 4c + (-6 * -3 + c * -3) = 2 + 2 + 2c 4c + (18 + -3c) = 2 + 2 + 2c Reorder the terms: 18 + 4c + -3c = 2 + 2 + 2c Combine like terms: 4c + -3c = 1c 18 + 1c = 2 + 2 + 2c Combine like terms: 2 + 2 = 4 18 + 1c = 4 + 2c Solving 18 + 1c = 4 + 2c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-2c' to each side of the equation. 18 + 1c + -2c = 4 + 2c + -2c Combine like terms: 1c + -2c = -1c 18 + -1c = 4 + 2c + -2c Combine like terms: 2c + -2c = 0 18 + -1c = 4 + 0 18 + -1c = 4 Add '-18' to each side of the equation. 18 + -18 + -1c = 4 + -18 Combine like terms: 18 + -18 = 0 0 + -1c = 4 + -18 -1c = 4 + -18 Combine like terms: 4 + -18 = -14 -1c = -14 Divide each side by '-1'. c = 14 Simplifying c = 14
| F(x)=(x+I)(x-I) | | 20-1=x-3 | | 8(k-6)+58=2(2k+5) | | 11/8(4x−8)−2=11/16(8x−12) | | Z-350=371 | | b-/2=4 | | 5x+2(11-4x)=8(-2t+11) | | 45-x=3 | | 3=(-6/x) | | -2(-2y+1)=-2y+22 | | 0.7-b=1.9 | | R/15=30 | | -1-5/8-8 | | 5(2c-3)=2c+5 | | 8n=n+42 | | X+Y=231 | | x+2=-2x-14 | | 16x-92=180 | | 5=x+31 | | -4-(-4)/3-6 | | 10y=-8 | | -324=27s | | (14x+7)-(-3x+2)= | | 4(3z-3)=9z-7 | | X+11x=156 | | 4x+8(-3x-3)=3 | | 12*48= | | 3-2/6-3 | | 25x^3y^4+50x^3y^4-75x^2y^3=0 | | x^2=2x-21 | | 3/4k-28=4 | | (12*4)+16= |